Malaysia's private University application platform - Lar, Kar Wai (2022)

(untitled)
This project is a web scraping project for Malaysia’s private universities. Applying to a university programme is the first step to pursue tertiary studies, and it is the starting point of the journey to the future. Nowadays, each private university offers a comprehensive list of undergraduate and postgraduate programme options in various fields. Selecting a study direction is a significant decision. Besides, individuals often face difficulty searching for related information to pursue tertiary studies. Therefore, this project is motivated to develop an effective platform that collects information on educational institutions’ programmes on a single website for students to ease the process of discovering universities and programmes. The platform is a web-based application that makes use of web scraping technology and the concept of data analysis to obtain required data from the universities’ websites on a real-time basis. Features that related to the tertiary studies are implemented into the web application as well. The features mentioned are search programme, view programme, manage favourite list, view history list and request recommendation. Therefore, users are able to get a list of relevant programme by using search programme and view the detailed information of interested programme. Moreover, users are allowed to export the programme information to users’ device. Different kinds of list are created to enhance conveniency as well as recommendation system is implemented to provide suggestion of area of studies. As a typical web application development project, Agile methodology has been adopted to focus more on coding and testing and thus develop an excellent quality and achieve project outcomes.